BolA-like protein (IbaG) promotes biofilm formation and pathogenicity of Vibrio parahaemolyticus - Wang, Wenchao; Li, Yangyang; Lu, Shuqi; Liu, Pengxuan; Han, Xiangan; Sun, Weidong; Wang, Quan; Fang, Weihuan; Jiang, Wei (Frontiers in Microbiology, 2024)
Vibrio parahaemolyticus is a gram-negative halophilic bacterium widespread in temperate and tropical coastal waters; it is considered to be the most frequent cause of Vibrio-associated gastroenteritis in many countries. BolA-like proteins, which reportedly affect various growth and metabolic processes including flagellar synthesis in bacteria, are widely conserved from prokaryotes to eukaryotes. However, the effects exerted by BolA-like proteins on V. parahaemolyticus remain unclear, and thus require further investigation. In this study, our purpose was to investigate the role played by BolA-like protein (IbaG) in the pathogenicity of V. parahaemolyticus. We used homologous recombination to obtain the deletion strain ΔibaG and investigated the biological role of BolA family protein IbaG in V. parahaemolyticus. Our results showed that IbaG is a bacterial transcription factor that negatively modulates swimming capacity.Furthermore, overexpressing IbaG enhanced the capabilities of V. parahaemolyticus for swarming and biofilm formation. In addition, inactivation of ibaG in V. parahaemolyticus SH112 impaired its capacity for colonizing the heart, liver, spleen, and kidneys, and reduced visceral tissue damage, thereby leading to diminished virulence, compared with the wild-type strain. Finally, RNA-sequencing revealed 53 upregulated and 71 downregulated genes in the deletion strain ΔibaG. KEGG enrichment analysis showed that the two-component system, quorum sensing, bacterial secretion system, and numerous amino acid metabolism pathways had been altered due to the inactivation of ibaG. The results of this study indicated that IbaG exerts a considerable effect on gene regulation, motility, biofilm formation, and pathogenicity of V. parahaemolyticus.To the best of our knowledge, this is the first systematic study on the role played by IbaG in V. parahaemolyticus infections. Thus, our findings may lead to a better understanding of the metabolic processes involved in bacterial infections and provide a basis for the prevention and control of such infections.